Bayt Ulhikmah’s Contribution To The Development Of Eastern Science - Alijonova Gulnoza (Periodica Journal, 2024)
This article provides information about the most famous scientific center of the Islamic world. Founded during the Abbasid dynasty, the center of science that brought together the most famous scientists in Baghdad and the entire Islamic world, contributed to the development of Islamic and secular sciences. Also, the contribution of the Abbasid dynasty to the development of science in the early Middle Ages, which occupied a large part of the earth's surface, and the scientific centers built by the Abbasid caliphs, are of great importance for their time and today. This article analyzes the contribution of the House of Wisdom to the Eastern Renaissance and the work of the scholars who worked there.
Keywords: Abbasids; Baghdad; Harun alRashid